A Study on the Analysis of Fundamental Motor Skills and Physical Activity Among Elementary School Students - Wibowo, Cahyo (Universitas Majalengka, 2024)
Background: Elementary school students gross motor skills and physical activity are crucial in shaping healthy lifestyles and children's physical development. Purpose: To describe gross motor skills and physical activity and ascertain the relationship between these variables. Methods: The research design employed in this study is an analytical observational approach utilizing a cross-sectional method. It involved 128 students selected through purposive sampling. The instruments used were (1) a gross motor skills assessment tool with a CVR value of 1, construct validity of 1, and reliability tested via test-retest method yielding α=0.708, and (2) the Physical Activity Questionnaire for Older Children (PAQ-C) with a reliability test result of α=0.84. Data analysis was conducted using descriptive techniques with percentages and Pearson correlation tests. Results: There is a significant relationship between gross motor skills and physical activity variables. The value of (p) is 0.000 < 0.05. The correlation coefficient (r) of 0.682 > 0.176 indicates a strong relationship between the two variables. Conclusion: This study elucidates a significant relationship between gross motor skills and physical activity among elementary school students Implications: These findings provide an essential impetus for teachers and parents to enhance their attention to children's physical fitness. Intervention measures targeting the enhancement of physical activity and the development of gross motor skills should be prioritized.